Walid Siti: The Black Tower - Siti, Walid (Berlin; Zilberman Gallery, 2017)
Catalog of an exhibition held at Zilberman Gallery from January 14-February 25, 2017. The Black Tower, curated by Nat Muller, is Walid Siti$1 (Bs first solo exhibition in Berlin. The title ofthe exhibition refers to the piece The Black Tower, which has the form of a collapsed spiral and isthus reminiscent of the famous minaret, al-malwiya, of the Great Mosque of Samarra, one of themost significant cultural monuments in Iraq fromthe 9th century CE. In the regional legends, the spiral-formed minaret was considered the brilliantidea of the Abbasid caliph Al-Mutawakkil, whohad been inspired while wrapping a piece of paperaround his finger in boredom during an audience. Text: Lotte Laub, Nat Muller, Nada Shabout, Rijin Sahakian. s
English; German
Keywords: N4390-5098 Visual Arts- Exhibitions